ON THE JOB TRAINING REPORT AIRPORT ELECTRICAL ENGINEERING STUDY PROGRAM DIPLOMA PROGRAM THREE BATCH XX AT SULTAN MAHMUD BADARUDDIN II AIRPORT PALEMBANG - Marbun, Laurenchius Irvan Freddy Marbun; Usman, Usman; Akbar, Muhammad Caesar (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The rapid development of Science and technology has resulted in electrical energy becoming a very important thing for humans. What would it be like if we lived without electricity, the use of electrical energy that is already very attached and touches many aspects of human life. Field Work Practice (On The Job Training) is carried out at the Airport that has been determined by the Medan Aviation Polytechnic Education Training. On The Job Training (OJT) is one of the curriculums that must be implemented by Cadets as a form of measuring the level of cadets' abilities in direct work practice and adding knowledge that has not been obtained from campus during the OJT period. After implementing On the Job Training (OJT) for approximately 6 months at Sultan Mahmud Badaruddin II Airport, Palembang, several conclusions can be drawn, including: The performance of the Aviation Electrical Unit which carries out its duties and responsibilities well. Can understand and gain experience and how the conditions or situations are in the world of work. Can develop the abilities possessed from the competencies obtained from the Airport. The author knows and understands the types of organizations, structures, units, and management at the Airport Can handle a problem in the field, and can find out the initial analysis of the problems that occur, so that they can handle the problem appropriately and efficiently